A new kinship typology and factors associated with receiving financial assistance in kinship care. (March 2020) - Xu, Yanfeng; Bright, Charlotte Lyn; Ahn, Haksoon; Huang, Hui; Shaw, Terry
Highlights: This study developed a new typology of kinship care based on financial assistance that families received. The typology included receiving TANF only, foster care payment (FC) only, TANF + FC, and None. The None group was further divided into None + Above Poverty and None + Below Poverty. The study examined factors associated with receiving TANF and foster care payments in kinship care. Abstract: Financial hardship is one of the most challenging issues faced by kinship foster care families. Temporary Assistance for Needy Families (TANF) benefits and foster care payments are potential sources of financial assistance for kinship families. This study used wave 2 of the National Survey of Child and Adolescent Well-Being II (NSCAW II) to develop a new typology of kinship care based on financial mechanisms, including: (1) families that received TANF only (TANF only); (2) families that received foster care payments only (FC only); (3) families that received both TANF benefits and foster care payments (TANF + FC); and (4) families that received no payments (None). This study further divided the None group into two subgroups: None + Below Poverty and None + Above Poverty. To examine factors associated with receiving TANF and foster care payments, results from logistic regression analyses indicated that maltreatment type, children's externalizing problems, married caregivers, and receiving social services were significantly associated with receiving foster care payments. Living below the federal poverty line and in a single-adult household were associated with receiving TANF benefits. Additionally, this study found that children of other race/ethnicity, such as Asian/ Pacific Islanders or Native American families, children's internalizing problems, and employed caregivers were associated with lower odds of receiving foster care payments. Being a licensed foster caregiver was associated with lower odds of receiving TANF benefits. The results suggest that child welfare workers and policy makers should consider how to increase kinship caregivers' awareness of financial resources and to make appropriate resources accessible for kinship caregivers.